Guns and Homicides: A Multiscale Geographically Weighted Instrumental Variables Approach. Issue 4 (23rd December 2019) - Bilgel, Firat
Abstract : This article assesses the locally varying effects of gun ownership levels on total and gun homicide rates in the contiguous United States using cross‐sectional county data for the period 2009–2015. Employing a multiscale geographically weighted instrumental variables regression that takes into account spatial nonstationarity in the processes and the endogenous nature of gun ownership levels, estimates show that gun ownership exerts spatially monotonically negative effects on total and gun homicide rates, indicating that there are no counties supporting the " more guns, more crime " hypothesis for these two highly important crime categories. The number of counties in the contiguous United States where the " more guns, less crime " hypothesis is confirmed is limited to at least 1258 counties (44.8% of the sample) with the strongest total homicide‐decreasing effects concentrated in southeastern Texas and the deep south . On the other hand, stricter state gun control laws exert spatially monotonically negative effects on gun homicide rates with the strongest effects concentrated in the southern tip of Texas extending toward the deep south .